Human Rights and Cybersecurity in Modern International Law - Zhailau, Zhanat; Adibayeva, Alina; Abdilda, Dilyana; Berkinbayev, Talgat; Nyssanbekova, Lyazzat (Law, State and Telecommunications Review, 2026)
[Purpose] The purpose of this study is to analyse the relationship between human rights and cybersecurity in the context of modern international law. The paper reviews key international legal acts and mechanisms aimed at protecting human rights in the digital age, and analyses the main challenges faced by the international community in the field of cybersecurity. [Methodology/approach/design] The study examines international standards related to the right to privacy and freedom of expression, enshrined in the European Convention on Human Rights. Special attention is paid to the issues of ensuring personal security from the point of view of international legal protection, and the role of international organisations such as the United Nations (UN) in protecting human rights in the face of increasing cyber threats. [Findings] It is determined that current international legal mechanisms are not always able to respond effectively to new challenges associated with the development of cyberspace, which can lead to human rights violations. The need to adapt existing international security tools to the specifics of the digital environment and develop new approaches for more effective protection of human rights in the digital age is identified. [Practical implications] The practical importance of the study is in the possibility of applying its findings in the development of international agreements and recommendations on the regulation of cyberspace, considering human rights; in the activities of international and regional organisations; in the development of cybersecurity strategies at the national level, accounting for international obligations; in the scientific and expert environment for further research and analytical work; and in the development of educational programmes for training specialists in the field of international law and cybersecurity. [Originality/value] The results obtained can be used to further improve international law and policy in the field of cybersecurity and human rights.